Y-shape optical fiber bundle in monitoring corrosion - Siaw, Wai San; Madzlan Aziz , Mohammad Ismail; Abd. Rahman, Rosly (Faculty of Civil Engineering, 2002)
Corrosion of the reinforcement is one of the major deterioration of reinforced concrete structures. The cause of corrosion can be either due to carbonation or chloride attack. The product of corrosion increases the reinforcement volume, hence causing cracking of concrete cover. With the advancement in the telecommunication industry, fiber optic has proven good track record to be resilient and durable to exposure even to extreme environment. The aim of this research is to look at the possibility of using fiber optic sensor to sense the occurrence of reinforcing steel corrosion. The Y-shape fiber optic bundle sensor was attached on a steel plate surface for corrosion determination. This corrosion sensor technique work is based on the detection of the colour changes of the steel plate surface from silvery to brown during the corrosion process. From the research, it was found that the Y-shape optical fiber corrosion sensor was capable to sense the occurrence of corrosion process in concrete